The order law of large numbers of the Marcinkiewicz - Zygmund - Akbash, K. S.; Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The Marcinkiewicz - Zygmund order law of large numbers is established for random variables in Banach lattices. Similar results are obtained also for the maximum scheme.